Insect molecular genetics : an introduction to principles and applications - Hoy, Marjorie A. (Academic Press, 2013)
This book summarizes and synthesizes two rather disparate disciplines-entomology and molecular genetics. It provides an introduction to the techniques and literature of molecular genetics; defines terminology; and reviews concepts, principles, and applications of these powerful tools.